Sustainable Urban Mobility: Current Strategies and New Challenges for European Cities - Galderisi, Adriana (TeMA - Journal of Land Use, Mobility and Environment, 2011)
In the decade 2001 – 2010 the European Union has undertaken taken numerous initiatives to guide the European cities toward sustainable mobility. The common purpose of the several initiatives implemented by the EU consisted in increasing, mainly in urban areas, mobility – unavoidable requirement for a competitive development of cities and for assuring better opportunities of access to urban services – and a contemporaneous drastic reduction of the heavy environmental costs that still now are associated with urban mobility. Strategies, initiatives and researches at European level have been addressed, during the decade 2001-2010, to promote a substantial limitation of current car-based mobility inside urban areas and to improve different forms of sustainable mobility. In detail, strategies and acitons have been mainly targeted to: - encourage innovations in the ways and means of urban transport; - assure an intermodal balance inside urban areas, improving public transport, above all rail transport, and pedestrian and bicycle travels; - overcome the segmentation that has long characterized transport planning, outlining governance processes based on the integration between policies and tools for city, transport and environment planning (Galderisi, 2007). Starting from 2007, the European Union has further and significantly increased its engagement in reducing the environmental cost of urban mobility. From the Green Paper on Urban Transport to the Covenant of Mayors aimed to actively involve the European cities in the path towards energy and environmental sustainability and, still, to the recent Transport White Paper 2011, several initiatives have been implemented by the European Union in order to effectively achieve the goals outlined in the White Paper 2001 and to define the future targets. Moreover, the new environmental challenges that the cities, not only the European ones, have to face in the future, from the climate changes to the growing costs and progressive oil reduction (a long-term although not negligible perspective), have helped to strengthen the centrality of urban mobility in scientific field. Besides, new research perspectives that frame the above-said topic of urban mobility into the wider theoretical framework of the “resilient” city are increasingly taking shape. Therefore, starting from a brief survey of the recent initiatives put forward by the European Union for sustainable urban mobility, this contribution focuses on the remarkable role that the concept of resilience plays in the present review of urban mobility policies and, mainly, in providing a decisive push towards an effective integration between governance of urban transformation and governance of mobility.